2022
DOI: 10.3390/pharmaceutics14020424
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and Compatibility Studies in the Development of Olmesartan Medoxomil and Hydrochlorothiazide Formulations under a Real Manufacturing Process

Abstract: A drug–drug and drug–excipient interactions and compatibilities study was conducted for two fixed-dose combination (FDC) products containing olmesartan medoxomil (OLM)/hydrochlorothiazide (HCT) 20/12.5 mg and OLM/HCT 40/12.5 mg during their development including storage. The study consisted of the evaluation of samples retrieved during all stages of a real manufacturing process. Powder X-ray diffraction (PXRD), differential scanning calorimetry (DSC), thermogravimetry (TGA), Fourier transform infrared spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…PXRD was used as a technique to monitor the excipient compatibility of API [ 27 , 31 , 32 ]. The initial PXRD fingerprints obtained from the study samples were used as a baseline to monitor if changes in the formulation would be detectable through changes in their diffractograms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PXRD was used as a technique to monitor the excipient compatibility of API [ 27 , 31 , 32 ]. The initial PXRD fingerprints obtained from the study samples were used as a baseline to monitor if changes in the formulation would be detectable through changes in their diffractograms.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study used PXRD and other isothermal techniques to establish compatibility between propafenone HCl and lactose monohydrate [ 29 ]. Further studies reported PXRD as one of the spectroscopic methods for conducting API using excipient assessments to support the stability data for pharmaceutical products [ 30 , 31 , 32 ]. As there is evidence to support using PXRD to monitor formulation changes in pharmaceutical development, this study employed the technique as a tool to possibly detect changes in the diffractograms of the L-T 4 formulations used in the stability studies.…”
Section: Introductionmentioning
confidence: 99%
“…Other characteristic bands of OLM are noticed at 1225 and 1167 cm −1 due to C-O stretching from lactone and ester groups, at 1551, 1503 and 1474 cm −1 assigned to C=C stretching vibration of the aromatic ring, at 1389 cm −1 due to C=N stretching vibration, at 1136 cm −1 attributed to C-O stretching vibration from tertiary alcohol, at 953, 826, 816, 781, 770 cm −1 corresponding to C ar -H bending. The C-N stretching vibration appears at 1302 cm −1 , the NNN bending vibration arises at 1002 cm −1 and the NH wagging is shown at 760 and 741 cm −1 [42,43].…”
Section: Ftir Spectroscopymentioning
confidence: 98%
“…[ 22 ] However, there are many published articles concerning its incompatibility with pharmaceutical ingredients due to its hydrophobic nature, the presence of the positively charged magnesium ion, and its strong surface energetic behavior. [ 23 24 25 ] Gelucire 48/16 is a member of the Gelucire family, is a mixture of mono, di, and triglycerides with PEG esters of fatty acids, working as nonionic surfactants and used in lipid-based formulations to increase solubility and bioavailability of poorly soluble drugs. [ 26 ] However, there is a lack of research data regarding their compatibility behavior toward drugs.…”
Section: Introductionmentioning
confidence: 99%